Budgetary Framework Reform in Green Transition in the EU and Germany - Fabio Botta; Christian Bender; Thomas Lenk; Mario Hesse (Intereconomics, 2024)
The proposal to amend Council Directive 2011/85/EU on the EU budgetary framework may result in changes in the role of environmental sustainability and explicitly the role of green budgeting in decision-making processes. While this topic is still in its infancy in Germany compared to other EU countries, there are some examples that show how green budgeting elements can be integrated in present budget procedures. The few German initiatives at the municipal level refer to very broad sustainability goals, rarely take comprehensive account of ecological impacts and are only extended to parts of the budget on a pilot basis: a genuine green budgeting concept has not been developed. With the focus on green budgeting, the EU is starting to push the climate policy agenda further. However, all international green budgeting practices show that it takes a considerable amount of time to implement a mature approach. Accordingly, time and effort will be needed for member states to adapt, conceptualise and expand approaches in the future.
Keywords: Q56; H23; H61; 330; Public budget; Environmental policy; Germany; EU countries; Öffentlicher Haushalt; Umweltpolitik; Deutschland; EU-Staaten